A systematic review on the safety of Mycobacterium tuberculosis-specific antigen-based skin tests for Tuberculosis infection compared with tuberculin skin tests - Hamada, Yohhei; Kontsevaya, Irina; Surkova, Elena; Wang, Ting Ting; Wan-Hsin, Liu; Matveev, Aleksandr; Ziganshina, Liliya Eugenevna; Denkinger, Claudia M.; Korobitsyn, Alexei; Ismail, Nazir; Abubakar, Ibrahim; Rangaka, Molebogeng X (Open Forum Infectious Diseases, 2023)
A systematic review showed that the accuracy of Mycobacterium tuberculosis antigen-based skin tests (TBSTs) for tuberculosis is similar to that of interferon γ release assay, but the safety of TBSTs has not been systematically reviewed.We searched for studies reporting injection site reactions (ISRs) and systemic adverse events associated with TBSTs. We searched Medline, Embase, e-library, the Chinese Biomedical Literature Database, and the China National Knowledge Infrastructure database for studies through 30 July 2021, and the database search was updated until 22 November 2022.We identified 7 studies for Cy-Tb (Serum Institute of India), 7 (including 2 found through the updated search) for C-TST (Anhui Zhifei Longcom), and 11 for Diaskintest (Generium). The pooled risk of any injection site reactions (ISRs) due to Cy-Tb (n = 2931; 5 studies) did not differ significantly from that for tuberculin skin tests (TSTs; risk ratio, 1.05 [95% confidence interval, .70-1.58]). More than 95% of ISRs were reported as mild or moderate; common ISRs included pain, itching, and rash. In 1 randomized controlled study, 49 of 153 participants (37.6%) given Cy-Tb experience any systemic adverse event (eg, fever and headache), compared with 56 of 149 participants (37.6%) given TST (risk ratio, 0.85 [95% confidence interval, .6-1.2]). In a randomized controlled study in China (n = 14 579), the frequency of systemic adverse events in participants given C-TST was similar to that for TST, and the frequency of ISRs was similar to or lower than that for TST. Reporting of the safety data on Diaskintest was not standardized, precluding meta-analysis.The safety profile of TBSTs appears similar to that of TSTs and is associated with mostly mild ISRs.
Gesehen am 07.07.2023